POSSIBILITIES OF PHARMACOLOGICAL CORRECTION OF STRUCTURAL AND FUNCTIONAL ALTERATIONS OF MICROCIRCULATION IN TERMS OF ENDOTHELIAL DYSFUNCTION IN COMORBID PATIENTS SUFFERED STROKE EVENT - I. A. Zolotovskaya; I. L. Davydkin (Klinicist)
Aim of the study – reveal clinical efficacy of naftidrofuryl in the aspect of correcting structural and functional changes of microcirculation (MC) in relation to the influence of the endothelial dysfunction (ED) parameters in comorbid patients suffered stroke event.Materials and methods. The study included 95 patients suffered ischemic type of stroke in the carotid bassin. An average age of patients was 69.0 ± 5.3 years, stroke duration was 73.5 ± 8.4 days. Patients were randomized in 2 groups by using blind method of envelopes. The mentioned groups matched on the main clinical and demographic characteristics. Patients from the 1st group (primary group, n = 47) were treated with naftidrofuryl (Duzofarm) at the daily dose of 300 mg, 2 patients (comparison group, n = 48) received basic therapy only. 50 people without an acute cerebrovascular accident in history were allocated as a control group (group 3). The following blood biochemical parameters were assessed: glucose, creatinine, total cholesterol, high density lipoprotein; triglycerides; markers of endothelial dysfunction: von Willebrand factor (VWF), tissue plasminogen activator inhibitor-1 (PAI 1), antithrombin III (AT III) and plasminogen. MC was studied by the method of laser doppler flowmetry. The duration of the observation period was 6 months, and 4 visits were performed during this period.Results. Initial task of group formation within the study protocol has been solved by us in a full range. Patients from Group 1 that received naftidrofuryl noted statistically significant differences after 3 and 6 months of follow-up observation. These differences reflected improvement in perfusion index, coefficient of variation, as well as endothelial, neurogenic and myogenic regulation of microvasculature, increase in perfusion oxygen saturation index in the microcirculation. We have found that an index of relative perfusion oxygen saturation in microvascular blood (Sm) being the main indicator that reflects oxygen saturation of microcirculation has significantly correlated with ejection fraction, PAI1, AT III, and plasminogen levels in group 1 patients in 3 and 6 months. We have also found significant correlation with ED when comparing parameters that express endothelial, neurogenic and myogenic regulation of microvessels. These data clearly demonstrated an association between improving of MC parameters and ED parameters in Group 1 patients.Conclusion. Possibility of correction of MC alterations leading to the worsening of ischemia and ED progression is one of the most promising directions in the treatment of stroke patients. Aim of the drug therapy is to prevent ED progression, reduced vascular tone and restore an adequate level of tissue hemoperfusion.